Neurologic Injury in Neonates with Congenital Heart Disease During Extracorporeal Membrane Oxygenation. Issue 1 (January 2015) - Polito, Angelo; Barrett, Cindy S.; Rycus, Peter T.; Favia, Isabella; Cogo, Paola E.; Thiagarajan, Ravi R.
<x xml:space="preserve">Abstract</x> The aim of this article is to describe the epidemiology and factors associated with acute neurologic injury in neonates with congenital heart disease (CHD) undergoing extracorporeal membrane oxygenation (ECMO). It is a retrospective cohort study. Multi-institutional data for purposes of this study were obtained from the extracorporeal life support organization registry Neonates with CHD supported with ECMO during 2005–2010. Of 1, 898 neonates with CHD supported with ECMO, 273 (14%) had neurologic injury. Birth weight less than 3 kg (odds ratio [OR]: 1.5; 95% confidence intervals [CI]: 1.1–1.9), pre-ECMO blood pH ⩽ 7.15 (OR: 1.5, 95% CI: 1.1–2.1) need for cardiopulmonary resuscitation before ECMO (OR: 1.7, 95% CI: 1.5–2.0) increased neurologic injury. In-hospital mortality was higher in patients with neurologic injury compared with those without (73% vs. 53%; p < 0.001). Neonates with CHD undergoing ECMO are highly vulnerable to acute neurologic injury regardless of cardiac lesion-specific physiology or the occurrence of cardiac surgery. The incidence of neurologic injuries in this population is higher in sicker patients. Severity of illness should therefore become the main target for improvement. Timely deployment of ECMO may therefore influence the development of ECMO complications.